The Arab and Jewish questions: geographies of engagement in Palestine and beyond - Bashir, Bashir; Farsakh, Leila (Religion, Culture, and Public Life, 2020)
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- Introduction THREE QUESTIONS THAT MAKE ONE BASHIR BASHIR AND LEILA FARSAKH -- PART I Interrogating Europe Anti-Semitism, Islamophobia, and Colonialism -- Chapter One JACKALS AND ARABS Once More on the German-Jewish Dialogue -- Chapter Two AN EMBLEMATIC EMBRACE New Europe, the Jewish State, and the Palestinian Question -- Chapter Three PALESTINE IN ALGERIA The Emergence of an Arab-Islamic Question in the Interwar Period -- PART II Beyond the Binary Division Between “Jews” and “Arabs” Revisiting National Constructs -- Chapter Four ON ORIENTALIST GENEALOGIES The Split Arab/Jew Figure Revisited -- Chapter Five RETURNING TO THE QUESTION OF EUROPE From the Standpoint of the Defeated -- Chapter Six BETWEEN SHARED HOMELAND TO NATIONAL HOME The Balfour Declaration from a Native Sephardic Perspective -- Chapter Seven TOWARD A FIELD OF ISRAEL/PALESTINE STUDIES -- Chapter Eight APOCALYPSE/EMNITY/DIALOGUE Negotiating the Depths -- Chapter Nine COMPETING MARXISMS, CESSATION OF (SETTLER) COLONIALISM, AND THE ONE-STATE SOLUTION IN ISRAEL-PALESTINE -- Chapter Ten DIALECTIC OF THE NATIONAL IDENTITIES IN PALESTINIAN SOCIETY AND ISRAELI SOCIETY Nationalism and Binationalism -- BIBLIOGRAPHY -- CONTRIBUTORS -- INDEX